A educação de pessoas jovens e adultas em Betim (MG), 1988-2007: perspectivas de educadores e professores de matemática - Ana Rafaela Correia Ferreira (2016)
In the present study, we elaborated comprehensions about the Mathematics teaching in the evening courses for young, adult and elderly students, offered by the Public Municipal System of Education in Betim (Minas Gerais) (Rede Pública Municipal de Educação de Betim - Minas Gerais) from the period of 1988 to 2007. Starting from the representations of 17 individuals, among teachers, educators and coordinators that acted in these courses, we discussed perceptions, believes, behavior patterns and strategies about teaching and learning Mathematics in the second segment of the Elementary School, in the Education of Young and Adult People Modality (Educação de Pessoas Jovens e Adultas - EJA). It was our interest to analyze how these professionals conceived their relationship with young and adult students, with the Mathematics and with the teaching and learning Mathematics in that teaching modality. We took as theoretical-methodological references studies of the Oral History and Cultural History. We underlay part of our analyses in Paulo Freire´s work, studies about EJA, teaching of Mathematics in EJA and curriculum. We presented a chronologic narrative of the many projects implanted for EJA that were developed in Betim during the referenced period and based in the constituted sources by the narratives of the collaborators and written documents, we wrote a story that emphasizes the ways those individuals conceived the Mathematical teaching, the evaluation prospects and the pedagogical strategies they used. The results founded evince the individuals wish and attempt of rethinking EJAs pedagogical and administrative organization, seeking a teaching that would attend the students demands, even with the adoption of pedagogical practices very similar to the ones performed in the regular teaching.